Redesigning assessment and accountability: An introduction - Elizabeth Leisy Stosich; Soung Bae; Jon Snyder (Education Policy Analysis Archives, 2018)
This special issue advances the discussion of redesigning assessment and accountability that began in the August 2014 Education Policy Analysis Archives article, “Accountability for college and career readiness: Developing a new paradigm” by Linda Darling-Hammond, Gene Wilhoit and Linda Pittenger. This issue focuses on the potential for multiple measures approaches to accountability and performance assessment to support more meaningful learning as part of a redesigned system of support and accountability. We bring together two reviews of state policy with commentaries that describe district, network, state, and university efforts to integrate multiple measures and performance assessment in systems of accountability. This issue helps to illustrate how educators at all levels of the system—schools, districts, networks, and state education agencies—are taking action to reimagine a more supportive and equitable educational system.